Information and digital literacies : a curricular guide for middle and high school librarians - Farmer, Lesley S. J. (Rowman & Littlefield, 2016)
"Information and Digital Literacies: A Curricular Guide for Middle and High School Librarians is a practical guide to help school librarians design and deliver effective instruction that addresses the knowledge, skills and dispositions of information and digital literacies. This curricular guide from one of America's foremost experts in this area will help librarians prepare students for college and careers. It provides systematic instruction about conducting research and using integration as stated in the Common Core, complying with state and federal mandates for digital safety/competence curriculum, and recognizing the instructional role of school librarians. It should be noted that 'canned' programs, particularly for digital safety exist, but they are not aligned with other school standards, and they do not reflect the unique communities of learners, let alone address the need to collaboration and articulation. The ready-to-implement curricular guide features: instructional design strategies, model middle and high school curriculum, including a scope-and-sequence, stand-alone courses, units of instruction, and sample learning activities, and ties to new AASL and ACRL information literacy standards, ISTE technology standards, 21st Century Partnership framework, and Common Core State Standards"--Provided by publisher